Telegram - Largo Caballero, Francisco, 1869-1946
011-0119-003 TELEGRAMS ACCEPTED FOR ALL PARTS OF THE WORLD except for the following European Countries : Belgium, Luxemburg, Danzig, Denmark, Esthonia Finance Germany, Holland, Latvia, Lithuania, Norway, Poland and Sweden AND FOR SHIPS AT SEA, AT THE COMPANY'S BRANCHES : - LONDON. CENTRAL TELEGRAPH STATION : Always Open. TOWER CHAMBERS, MOORGATE, E.C.2. Telegraphic Address: Signally Ave., London. , METropolltan 6666 (40 lines ). Telephone Numbers _ 6644 20 lines Phonograms. BRANCH OFFICES :— Telephone Numbers. The Baltic Exchange, Bury Street, E.C.3 18, Old Broad Street, E.C.1 Candlewick House, 116-126, Cannon Street, E.C.4 ........... 34. Leadenhall Street. E.C.3 Cereal House, 58, Mark Lane, E.C.3 The Fruit Exchange, Spitalfields Market, E. 1 24, Royal Exchange, E.C.3 Shorters Court. Throgmorton St., E.C.2 3-5, Charterhouse Street, E.C.1 6, Denman Street, Borough, S.E.1 . ... Electra House, Victoria Embankment, W.C.2 41 and 42. Parliament Street, S.W.1 Thos. Cook & Son Ltd., Main Office, 43, Berkeley Street. W.1 Cumberland Hotel. Marble Arch ..... 20. Swallow Street. W.1 35. Southampton Street, Strand. W.C.2 Golden Cross House, Charing Cross, Strand, W.C.2 LONdon Wall 4811 HOLborn 4755 HOP 0818 2 lines) TEMple Bar 1353 WHItehall 2441 (2 lines) MAYfair 4587 AMBaasador 1234 REGent 6244 (3 lines: TEMple Bar 1353 WHItehall 3696 PROVINCES. Telephone numbers Midland 5081 (6 lines) Bradford 6007 ( 3 lines) Edinburgh 25068 Central 7760 (4 lines) Central 358[...] Leeds 21518 (2 Lines) Central 3223 (10 lines) Newcastle (3 lines ) St. Buryat[...] Sheffield 20283 Southampton 302[...] METropolltan 6666 Birmingham 2 : Guildhall Buildings, Pinfold street Bradford : 4, Commercial Street...... Dundee : 46 and 50, Bell Street Edinburgh : 42, George Street (rear block) Glasgow C.1 : 40, Royal Exchange Square Hull : 76, Lowgate Leeds 1 : KingStreet Chambers,52,Wellington Street Leith : 64, Constitution Street Liverpool 2 : India Buildings, Brunswick Sreet The Cotton Exchange „ The Fruit Exchange Manchester 2 : 55, Spring Gardens Newcastle : 31, Mosley Street ...... Princes Buildings, 1, Queen street Porthcurno : Cornwall Sheffield 3 : 50, The Wicker......... Southampton : Southwestern Chambers, Canute Road.................. It is recomended that telegrams be handed direct to the Company's Branches as above. Receipts are given gratis for the amount charged. Telegrams for this Company's system are also received at all Postal Telegraph Offices, but should be marked "VIA IMPERIAL CABLE " if intended for transmission by cable, or " VIA IMPERIAL WIRELESS " if intended for transmission by wireless. This indication is not charged for TELEGRAPHIC ADDRESSES REGISTERED FREE OF COST. Books of telegrams forms, Tariffs, Rules, etc., can be obtained at the Head Othces ot the Company, or at any of the above-named branches. IRISH FREE STATE. DUBLIN : 67, Middle Abbey Street (Inquiry Office only) Telephone No. : Dublin 44995 Head Office of the Company :—ELECTRA HOUSE, VICTORIA EMBANKMENT, LONDON, W.C. 2. Telegraphic Address : EMPIREGRAM ESTRAND. Telephone: TEMpleBar 1222. 292/946/11/120(ii)